1994
DOI: 10.1111/j.1574-6968.1994.tb07048.x
|View full text |Cite
|
Sign up to set email alerts
|

Buffering capacity and membrane H+conductance of lactic acid bacteria

Abstract: Buffering capacity and membrane conductance to H+ were measured in Enterococcus faecalis and Lactobacillus acidophilus by a pulse technique. The magnitude of these parameters varied between one species and another. Over the pH range studied, from pH 3.72 to 7.74, the acidophile Lactobacillus acidophilus showed higher values of buffering capacity and membrane H+ conductance than the neutrophile Enterococcus faecalis. These results support the idea that acidophiles have high cytoplasmic buffering capacity, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…Reported values of ' passive ' proton conductance in Gram-positive species are less than 1 mmol H + (g protein) −" h −" (Maloney, 1979 ;Rius & Lore! n, 1998 ;Rius et al, 1994 ;Bender et al, 1986). However, S. bovis had an ATP hydrolysis rate of 39 mmol ATP (g protein) −" h −" , and based on a ratio of protons pumped\ATP of 4, the proton conductance of S. bovis was 156 mmol H + (g protein) −" h −" , a value…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reported values of ' passive ' proton conductance in Gram-positive species are less than 1 mmol H + (g protein) −" h −" (Maloney, 1979 ;Rius & Lore! n, 1998 ;Rius et al, 1994 ;Bender et al, 1986). However, S. bovis had an ATP hydrolysis rate of 39 mmol ATP (g protein) −" h −" , and based on a ratio of protons pumped\ATP of 4, the proton conductance of S. bovis was 156 mmol H + (g protein) −" h −" , a value…”
Section: Discussionmentioning
confidence: 99%
“…n, 1998 ;Rius et al, 1994 ;Bender et al, 1986). These discrepancies can be explained by the non-ohmic relationship between proton conductance and driving force.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies reported that the low pH is the most important factor affecting the viability of L. acidophilus (most common Lactobacillus species incorporated in commercial yogurts in the US) and Bifidobacterium species (Laroia and Martin, 1991;Shah and Ravula, 2000) post-fermentation. On the other hand, Ruis et al (1994) pointed that L. acidophilus has a high cytoplasmic buffering capacity (pH 3.72-7.74), which allows it to resist changes in intracellular pH and therefore gain stability under acidic conditions. However, this effect has not been documented universally for all strains.…”
Section: Factors Affecting the Survival Of Probioticsmentioning
confidence: 99%